Examining Cultural Equity: Boston’s Arts & Culture Sector - Brown, Marian Taylor (ProQuest Dissertations & Theses, 2020)
There is a cultural equity gap within the United States’ arts and culture landscape, constituting unequal representation of various identities in the arts, including, race, disability, gender, sexual orientation, and socioeconomic status. These inequities reproduce within arts management, academia, artist sales, and donor and foundation demographics and priorities. With the objective of working toward creative justice in Boston’s arts and culture sector, this multiphase study employs transdisciplinary research using inductive, mixed-methods to learn: 1) current influencers’ understanding of the cultural equity gap; 2) current influencers’ motivations to eradicate the cultural equity gap; 3) how arts leaders with various marginalized identities conceptualize and operationalize leadership development for themselves; and 4) how arts leaders with various marginalized identities perceive barriers to access for positions of leadership in the arts and culture sector. These nuanced investigations support the foundational question: What are the social, emotional, economic, and cultural assets within Boston that can lead to creative justice and what reformation is still needed to achieve creative justice? Findings include attitudes and beliefs surrounding cultural equity, examination of historical and present-day oppressive structures, pipeline talent issues and opportunities, levers for change in building equity, and a call for culture shift.